2017
DOI: 10.1016/j.jnucmat.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties examined by nanoindentation for selected phases relevant to the development of monolithic uranium-molybdenum metallic fuels

Abstract: Nanomechanical properties, specifically the reduced modulus and hardness of several intermetallic and solid solution phases are reported to assist the development of the U-10 wt.% Mo (U-10Mo) monolithic fuel system for research and test reactors. Findings from this study and reported values of mechanical properties provide data critical for understanding and predicting the structural behavior of the fuel system during fabrication and irradiation. The phases examined are products of interdiffusion and reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Figure 8 showed hardness dependence on depth which were took as the average of 6 points indents. The hardness for U was close to that determined by Newell [17] as shown in Table 2. But there was no hardness value for U-Cu intermetallic compound found in references to compare.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 8 showed hardness dependence on depth which were took as the average of 6 points indents. The hardness for U was close to that determined by Newell [17] as shown in Table 2. But there was no hardness value for U-Cu intermetallic compound found in references to compare.…”
Section: Resultssupporting
confidence: 87%
“…By fitting Equation (1) and applying a typical Poisson’s ratio for uranium( v s = 0.25) [9], the Young’s modulus of Uranium, E s was calculated as 160 ± 5 GPa. While an assumed value of 0.3 was employed for Poisson’s ratio of UCu 5 due to lack of the data in literature as Ryan Newell [17] has done, then the Young’s modulus of UCu 5 , E s was calculated as 121 ± 8 GPa. A comparison of Young’s modulus was made between this work and other’s work like Beeler [18], Wheeler [19], and Yamanaka [9], which indicated that the magnitude of Young’s modulus of U-Cu alloy was not markedly different from other uranium intermetallic compounds and uranium.…”
Section: Resultsmentioning
confidence: 99%
“…Indentations were spaced at least 10 times the indentation depth apart to avoid the strain field of previous indents. Data were analyzed using the InView analysis software with a Poisson ratio of .33 (Waldron et al, 1958;Newell et al, 2017;Hu and Beeler, 2021).…”
Section: Preirradiation Characterizationmentioning
confidence: 99%
“…Although some gamma phase stability can be achieved with low concentrations of Mo, 10 wt % Mo additions notably improve stability of the meta-stable γ-U phase that may remain stable under irradiation due to the stabilizing effect of ballistic mixing (Dwight, 1960;Rest et al, 2006;MEYER et al, 2014;Newell et al, 2020;Lu et al, 2021). Irradiation testing has been performed on U-10Mo and U-7Mo alloys for research reactor applications under 250 °C (Waldron et al, 1958;Dwight, 1960;May 1962;Leenaers et al, 2004;Rest et al, 2006;Creasy, 2012;Smirnova et al, 2015;Newell et al, 2017;Kautz et al, 2021;Gates et al, 2019) and for higher temperature fast reactors (Walters et al, 1984;Kittel et al, 1993;Harp et al, 2018) above 500 °C. Irradiation testing in the low and high temperature regimes showed initial linear swelling followed by breakaway fission gas-induced swelling, coincident with grain recrystallization above a fission density of 2-7 × 10 21 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…To comply with nuclear non-proliferation requirements (Hanson and Diamond, 2011;Woolstenhulme and Nielson, 2011;Robinson et al, 2013), low enriched uranium (LEU) fuels need to be utilized for advanced research and test reactors. Monolithic U-Mo fuels have been demonstrated to be attractive candidates because of their low neutron capture cross section, high uranium density, stable irradiation swelling performance (Burkes et al, 2009;Robinson et al, 2013;Mei et al, 2015;Newell et al, 2017). Rectangular fuel assemblies (Brown et al, 2013;Wu et al, 2017) can be made by connecting a number of U-Mo/Al monolithic fuel plates (Cheng et al, 2004;Perez et al, 2011;Robinson et al, 2013;Turkoglu et al, 2019) with an Al alloy frame, using the processing method of rolling-swage.…”
Section: Introductionmentioning
confidence: 99%